Localized Acral Sclerosing Langerhans Cell Histiocytosis: A New Form of Presentation of Cutaneous Langerhans Cell Histiocytosis. (May 2020) - Garrido, Maria C.; Salido-Vallejo, Rafael; Revilla, Enrique; Salvatierra, Juan; Rodriguez-Peralto, Jose-Luis
Abstract : Abstract: Langerhans cell histiocytosis (LCH) is a rare proliferative disorder, more frequent in children, characterized by an abnormal accumulation of Langerhans cells admixed with eosinophils, lymphocytes, neutrophils, and macrophages. The clinical presentation is variable and depends on whether a single or multiple organs are affected. Skin lesions are common in LCH (40% of cases) and represent a frequent form of presentation (in up to 80% of cases). Cutaneous manifestations of LCH are highly variable, frequently presenting as crusted papules or scaly seborrheic-like lesions localized in the scalp. We report the first case of a localized acral sclerosing LCH, a new form of LCH. This case highlights the broad and surprising form of presentation of LCH which may be overlooked and can significantly delay its diagnosis. The development of systemic disease may occur months to years after the initial skin presentation. Prompt diagnosis and treatment may prevent progression to systemic disease, as documented in some cases.